Ultralow-Dose Adjunctive Methadone with Slow Titration, Considering Long Half-Life, for Outpatients with Cancer-Related Pain - Srini Chary; Amane Abdul-Razzak; Lyle Galloway (Palliative Medicine Reports, 2020)
Background: The unique properties of methadone make it attractive for use in cancer pain. The use of very low initial doses of adjunctive methadone is a promising strategy given its simplicity and potentially reduced risk profile. Objective: To understand if an ultralow-dose (ULD) methadone protocol (1?mg by mouth daily initial dose with gradual titration) can improve pain control in outpatients with cancer-related pain not responsive to previous opioids and/or nonopioid analgesics. We also sought to assess if the use of ULD methadone resulted in improvement in mood and sleep among other outcomes. Design and Setting/Subjects: This study is a retrospective chart review of outpatients at the cancer pain clinic at the Tom Baker Cancer Centre in Calgary, Alberta, Canada. Measurements: The mean ratings in maximum and average pain before methadone initiation, and at the final follow-up point are reported. Paired sample t tests evaluate for statistically significant differences in pain ratings before methadone initiation and at final follow-up. We also report the proportion of participants with a subjective improvement in pain, sleep, and mood (dichotomous ?yes/no?), and the mean number of weeks to initial documented pain improvement. Results: 68.6% of patients (24/34) reported a subjective improvement in pain. Most patients reported improved sleep and mood (78.8% and 64.7%, respectively). Conclusions: More than two-thirds of patients reported an improvement in pain with a protocol using very low initial doses of adjunctive methadone. Our report is a preliminary retrospective chart review and larger prospective trials are warranted.